Bond–slip constitutive relation of mortar anchor under different loading rates. Issue 4 (23rd January 2020) - Wang, Haitao; Guo, Tao; Sun, Haoyu
Abstract : Purpose: This paper aims to focus on establishing the bond-slip constitutive relation of mortar anchor under high loading rates by the dynamic pull-out test. Design/methodology/approach: Self-made specimens were made for the dynamic pull-out test to explore the bond performance of mortar anchor, and the bond-slip constitutive relation of mortar anchor under high loading rates was established according to the analysis of test data. Findings: During the loading process, the position of the peak bond stress was observed to translate to the free end. The bearing capacity of the mortar anchor was enhanced to some extent due to the increase of the loading rate. Originality/value: The bond-slip constitutive relation of mortar anchor under high loading rates was established with the introduction of the position function and dynamic-load expanded coefficient.